2018
DOI: 10.1093/annonc/mdy425.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of first-line ceritinib and alectinib in advanced ALK+ NSCLC: A cross-study indirect comparison

Abstract: Background: The efficacy of continuing anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) beyond initial disease progression for ALK-positive patients with advanced non-small cell lung cancer (NSCLC) has not been fully understood. Methods: We retrospectively analyzed 74 ALK-positive advanced NSCLC patients who received ALK-TKIs between August 2011 and July 2017 in Kumamoto university hospital and community hospitals in Japan. Continuation of ALK-TKIs beyond progressive disease (PD) was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, in single-arm trial comparative study of alectinib versus ceritinib, median OS with alectinib was prolonged 24.3 vs 15.6 with ceritinib; HR: 0.65; 95% CI: 0.48–0.88 ( 29 ). It was also confirmed by the recently published cross-study indirect comparison, which demonstrated 22% lower hazard ratio compared to ceritinib; HR: 0.78 ( 30 ).…”
Section: Introductionsupporting
confidence: 60%
“…However, in single-arm trial comparative study of alectinib versus ceritinib, median OS with alectinib was prolonged 24.3 vs 15.6 with ceritinib; HR: 0.65; 95% CI: 0.48–0.88 ( 29 ). It was also confirmed by the recently published cross-study indirect comparison, which demonstrated 22% lower hazard ratio compared to ceritinib; HR: 0.78 ( 30 ).…”
Section: Introductionsupporting
confidence: 60%